MIXED MODE CATION EXCHANGE CHROMATOGRAPHY LIGANDS BASED ON 1,3-DIOXOISOINDOLIN-2-YL STRUCTURES - BELISLE, Christopher; LOZANO, Edwin; LIAO, Jiali (2022)
The subject invention pertains to proteins are purified by a mixed-mode chromatography system formed by attaching a ligand with cation exchange and hydrophobic l,3-droxoisoindolin-2-yl group functionalities to a large-pore support matrix, the only linkage between the ligand and the support matrix being a chain having a backbone of one, two, three, four, or five atoms between the hydrophobic group and the support matrix. La présente invention concerne des protéines purifiées par un système de chromatographie en mode mixte formé par la fixation d'un ligand avec des fonctions d'échange cationique et de groupe hydrophobe 1,3-dioxoisoindoline-2-yle à une matrice de support à larges pores, la seule liaison entre le ligand et la matrice de support étant une chaîne ayant un squelette d'un, deux, trois, quatre ou cinq atomes entre le groupe hydrophobe et la matrice de support.